Talent Retention Practices Adopted by the Automobile Companies with Special Reference to Chennai (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2024)
Purpose: This study aims to understand Talent retention Practices adopted in Automobile companies with special reference to Chennai.Methodology: The study is descriptive research by nature. It enables the researcher to summarize and organize data in an effective and meaningful way.Findings: The five dimensions of talent retention namely “Pressure at work, following the procedure, retaining culture, training, and job satisfaction were assessed in the automobile sector. The results show that employees are facing pressure at work, given adequate authority, skill enhancement possibilities, and a high level of Job security.Originality/Value: This article assesses the talent retention practices adopted in the automobile sector. This study explores the employee retention dimensions and recorded the responses of four hundred employees.Paper type: Descriptive research
Keywords: Automobile sector; Talent; Retention; Descriptive; Pressure at Work; culture and Job satisfaction